2013
DOI: 10.1080/15567030903077980
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Micellar Effect on Photogalvanics: Solar Energy Conversion and Storage—EDTA-Safranine O-NaLS System

Abstract: The studies of the micellar effect on photogalvanics were done for solar energy conversion and storage in photogalvanic cell containing sodium lauryl sulphate as anionic micellar species, ethylenediamine tetra acetic acid as reductant, and Safranine O as photosensitizer. The photopotential and photocurrent generated were 871.8 mV and 200.0 A, respectively. The observed conversion efficiency was 0.7213%, the fill factor was 0.35, and the maximum power of the cell was 174.2 W, whereas the power at the power poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The power reaches a maximum value at 0.46 M alkali concentration, and at alkali concentrations higher than 0.46 M, the cell power starts decreasing (Figure 7). This has also been observed in prior studies that the performance of the cell increases with increase in the alkalinity, and cell power reaches a maximum value at the optimal alkali concentration 8,9,12,31,32 . As the concentration of NaOH increase so does the pH of the solution.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The power reaches a maximum value at 0.46 M alkali concentration, and at alkali concentrations higher than 0.46 M, the cell power starts decreasing (Figure 7). This has also been observed in prior studies that the performance of the cell increases with increase in the alkalinity, and cell power reaches a maximum value at the optimal alkali concentration 8,9,12,31,32 . As the concentration of NaOH increase so does the pH of the solution.…”
Section: Resultssupporting
confidence: 79%
“…The endeavor to continuously improve and optimize photogalvanic cell by using different dye sensitizers, reductants, and surfactants has been a consistent effort by researchers. Various dye photo‐sensitizers (such as the Bromophenol Red, 3 Congo Red, 4 Azur B, 5 Methylene Blue, 6 Brilliant Cresyl Blue, 7 Rose Bengal, 8 Safranine O, 9,10 Indigo Carmine, 11 Sudan‐I, 12 Rhodamine B, 7 Fast Green FCF, 13 Metanil Yellow, 14 mixed dyes, 15 Eosin, 16 Toluidine blue, 17 etc.) and similarly different reductants (like ethylenediamine tetra acetic acid, 5,6 formic acid, 11 fructose, 12 Fe +2 , 18 sugars, 16 D‐Xylose, 17 etc.)…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that SLS is very effective in enhancing CE of cell, and have shown effect of raising CE up to two times of CE observed in its absence. The Gangotri has reported CE 0.72 % in presence of SLS, and CE 0.33 % in absence of SLS. Thus, the increase in CE from 7.58 % to 11.28 % (∼ 1.5 times) in present work is not unexpected.…”
Section: Resultsmentioning
confidence: 96%
“…Gangotri and Gangotri [26] have studied the effect of diffusion length (distance between the electrodes) in photogalvanic cells. The effect of varying the diffusion length on the electrical output (I max , I eq ) and initial rate of current generation in the photogalvanic cell can be observed by using H-cells of different dimensions.…”
Section: Effect Of Diffusion Length On the Systemmentioning
confidence: 99%